Voltage profile improvement of weak grid with solar PV integration - Sandeep Vuddanti; Varun N. John; Surender Reddy Salkuti (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
The objective of this paper is to improve the voltage profile of the grid in pertinence to grid due to power injection from distributed solar photovoltaic (PV) arrays. Weak grids are modeled as worldwide adaptation of net metering, transactive energy systems, and the possibility of further deterioration of power quality with higher grid penetration. In this paper, a solar PV integrated weak distribution grid modelled as the PV arrays being frequently connected in rural areas, due to various reasons like cheap real estate and lack of accessibility. In this paper, three case studies of PV generation are simulated, i.e., scheduled solar PV generation less than load requirement, PV generation equal to load requirement, and PV generation more than load requirement, by considering the daily solar irradiation and load demand profiles of a residential area under study.